Keefektifan Media Aplikasi Karya Karsa dalam Pembelajaran Membaca Cerpen dan Implementasinya terhadap Kurikulum Merdeka pada siswa kelas XI SMA N 01 Wanasari - Sri Kurnia; Hany Uswatun Nisa; Ghufroni Ghufroni (Journal on Education, 2024)
Curriculum in the world of education can be likened to a public vehicle that carries passengers to their destination. Based on this, this vehicle must first be designed with equipment, materials and other equipment and must also prioritize appropriateness standards for carrying passengers to reach their destination. The aims of this research are (1) to describe learning to read short stories without using the Karya Karsa application media (2) to describe how learning to read short stories uses the Karya Karsa application media (3) to test the effectiveness of the Karya Karsa application media in learning to read short stories and its implementation. towards the independent curriculum for class XI students at SMA N 01 Wanasari. This research uses quantitative methods. Data collection in this research used test instruments. The results of this research are (1) Learning to read short stories without using the work of karsa application media is not effective in learning to read short stories, the results of learning to read short stories in the control class have a lower average score than the experimental class. (2) In learning to read short stories using the Karya Karsa application, there is a significant difference in the average "student grades" between the two groups. This difference was large enough to be considered significant, with the first group having a lower mean value compared to the second group, with the 95% confidence interval for the difference not including a value of zero. (3) The effectiveness of the Karya Karsa application on the ability to read short stories is very significant. This is proven by the t count of 2,143 which is greater than the t table of 0.063 with 72 respondents.